The Impact of Smartphone Addiction on Learning Outcomes Between Male and Female University Students - Yanti, Fitri; Wijaya, Tony; Sholeh, Maimun (Jurnal Ilmiah Peuradeun, 2024)
This study analyzed the impact of smartphone addiction on learning outcomes between males and females on learning outcomes. Several studies have analyzed the effects of smartphone addiction on student learning effectiveness. However, there are a lot of gaps in these studies, such as the selected sample, in which all the respondents are assumed to belong to a gender group. In this work, we categorize each respondent, based on gender, into male and female. 500 students from public and private universities in Indonesia participated in this study. The independent-sample t-test, linear correlation, and regression analysis determined the result. It was found that smartphone addiction had a significant negative correlation with learning outcomes in male students and no significant correlation in female students. Male students’ smartphone addiction had a higher effect on learning outcomes than females, with a percentage of 33.7%. This study contributes to improving the gender perspective on learning issues.